Influence of drinking structured water on production performance, nutrient retention, carcass characteristics and economics in commercial broiler chicken - VASANTHAKUMAR, P; CHANDRASEKARAN, D; PURUSHOTHAMAN, M R; KATHIRVELAN, C; JANANI, S R; SENTHILKUMAR, S (The Indian Journal of Animal Sciences, 2017)
Water from open and bore well are commonly used in majority of the poultry farms in India. When the drinking water is passed through specially designed apparatus in which tuned geometry creates an energy environment for the water to structure itself, it is claimed that surface tension of water is lowered with better hydrating properties. This geometric technology said to break up large low energy water molecule clusters into smaller high energy clusters which is called as structured water or structure-altered water. In order to study the influence of structured water on the performance of commercial broiler chicken, an experiment was conducted using 216 numbers of Vencobb broiler chicks up to 42 days of age. The birds were assigned to two groups comprising of twelve replicates per group with 9 birds per replicate. The control group (108) was offered tap water whereas the treatment group was offered structured water for drinking purpose. The body weight (g) was numerically higher in structured water group (2016 ± 28 vs 1989 ± 26) as compared to tap water offered group. Similarly, the feed conversion efficiency was relatively better (1.769 ± 0.02 vs 1.802 ± 0.02) in structured water group. The total quantity of water consumed (ml/bird) up to 6 weeks age was less in structured water group (11511±144) as compared to the tap water (11101±112) offered group. The digestibility of nutrients and retention of minerals were similar among the tap and structured water offered groups. The heart (10.12b±0.34 vs 9.16a±0.20) and spleen weights (2.73b±0.012 vs 1.817a±0.005) were significantly high and abdominal fat content was low (1.021a±0.055 vs 1.204b±0.061) in structured water group as compared to tap water offered group. The feed cost per kg body weight gain was comparatively low (Rupees 1.03) in structured water group (Rupees 54.88 ± 0.55 vs 55.91 ± 0.48). From this study, it can be inferred that structured water offered to commercial broiler chicken for drinking purpose resulted in extra profit of `2.06/bird.